2009
DOI: 10.1007/s12272-009-1316-9
|View full text |Cite
|
Sign up to set email alerts
|

A novel in vitro ischemia/reperfusion injury model

Abstract: The reperfusion of blood flow occurred in a number of conditions such as stroke and organ transplantation immensely augments tissue injury and causes more severe damage than prolonged ischemia. In the present study, we designed a novel double-layer parallel-plate flow chamber (PPFC) to develop an in vitro ischemia/reperfusion (I/R) injury model and examined the effects of I/R on inflammatory responses in human microvascular endothelial cells (HMEC-1). The expression of pro-inflammatory mediators, such as inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…While our results aligned with previous animal and in vitro studies [36][37][38], studies using rodent as animal model for IRI also showed an increase in the levels of ICAM-1 on EC membrane [37] and in leukocyte adhesion to EC after IRI [36]. Hence, we were able to recapitulate certain feature of IRI as seen in in vivo studies.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…While our results aligned with previous animal and in vitro studies [36][37][38], studies using rodent as animal model for IRI also showed an increase in the levels of ICAM-1 on EC membrane [37] and in leukocyte adhesion to EC after IRI [36]. Hence, we were able to recapitulate certain feature of IRI as seen in in vivo studies.…”
Section: Discussionsupporting
confidence: 90%
“…Hence, we were able to recapitulate certain feature of IRI as seen in in vivo studies. Other in vitro model of IRI also exhibited higher levels of ICAM-1 after reperfusion [38]. However, this study induced ischemia in artificial manner.…”
Section: Discussionmentioning
confidence: 60%
“…Dynamic test results further showed that rapid (<130 seconds) and reversible (<0.3% O 2 deviation) hypoxic conditions (from 12.6% to 1.2% oxygen tension) can be induced by changing the distance between the cells and biomaterials from 200 μm to 1200 μm. The results highlighted the potential of the developed hypoxia insert to be used for in vitro hypoxia / reoxygenation model of ischemia-reperfusion injury [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conventional in vitro models for tissues generate an ischemic environment in 2D cultures by using a hypoxia chamber and a nutrient‐poor culture medium to define the amount of nutrients available to cells . These systems have provided a plethora of information about the responses of cells to ischemia (i.e., viability, changes in metabolism, release of free radicals), including the elucidation of many ischemia‐related pathways . The culture conditions in these 2D models, however, provide information about the effects of global ischemia but not those resulting from the physiological gradients formed in a tissue.…”
Section: Introductionmentioning
confidence: 99%